Pendampingan Pembelajaran Matematika pada Warga Belajar di SKB Posko Karangbesuki - Dian Fitri Argarini; Sri Wahyu Setyaningsih; Susilo Bekti (Jurnal Dremi (Demi Pengabdi Masyarakat), 2026)
Low motivation to learn and limited learning support are challenges faced by Package B learners at the SKB Posko Karangbesuki. These conditions make it difficult for learners to understand the mathematics material. This community service activity aims to improve the learning motivation and understanding of mathematics material among Package B learners through mathematics learning support activities. The implementation methods include the preparation, implementation, and evaluation stages. The preparation stage involves identifying learning needs and coordinating with the institution. The implementation stage involves direct learning support, material explanations, discussions and Q&A sessions, as well as practice problems. The evaluation phase involved observing attendance, participation, and problem-solving performance. The results of the activity showed an increase in learning motivation, marked by more consistent attendance and more active participation in learning. Learners’ understanding of mathematics material also improved, as evidenced by their ability to solve problems effectively. The mathematics learning support activity has proven to be an effective strategy for improving the quality of learning in Package B equivalency education